دور القاضي في الدفع بعدم الدستورية - بوحفص عبد الرحيم (University Of Eloued جامعة الوادي, 2024)
تتناول هذه الدراسة دور القاضي في آلية الدفع بعدم الدستورية في فرنسا وبالدول المغاربية تحديدا الجزائر، المغرب وتونس، والتي أحدثت تغييرا جذريا فيما يخص ممارسة جهة الرقابة الدستورية، لاختصاصها لاسيما طريق الإحالة عليها كآلية للإخطار عن طريق تفعيل العدالة الدستورية ، بمجرد إثارتها من قبل المتقاضي أمام جهة القضاء المطروح أمامها النزاع للدفع بعدم دستورية الحكم التشريعي أو التنظيمي بهدف استبعاده من التطبيق لانتهاكه الحقوق والحريات التي يضمنها الدستور، أو أنه يشكل أساسا للمتابعة الجزائية، وخلالها يلعب قاضي الموضوع (العادي والإداري) في كل من فرنسا، الجزائر والمغرب دوراً محورياً في إيصالها لجهة القضاء الدستوري. باعتبار الدفع آلية إجرائية يشرف عليها القاضي، عن طريق نظام التصفية الأولية المزدوجة للدفع على مستوى الجهات القضائية الدنيا والعليا. يتمتع قاضي الموضوع بمجموعة من السلطات لإرسال الدفع للجهة القضائية العليا أو إحالته من قبل هذه الأخيرة على جهة الرقابة الدستورية من عدمه، فسلطته تتسع عند مراقبة الشروط الشكلية، في حين أنها تتقيد وتضيق عند مراقبة الشروط الموضوعية، لاسيما إعمال سلطته التقديرية والتفسيرية أثناء تقديره قيام شرط جدية الدفع التي تتم تحت رقابة الجهة القضائية العليا باعتبارها الجهة المقومة لأحكامه، وكذا الجهة المكلفة بالرقابة الدستورية باعتبارها الجهة المختصة بالفصل في مسألة الدستورية، لأن سلطته التقديرية مقيدة بالضوابط المقررة في نص الدستور والقوانين العضوية، في حين أن سلطته التفسيرية بتطبيق أساليب وتقنيات التفسير الدستوري تنحصر على الناحية الظاهرية دون التعمق فيها لدرجة حسم مسألة الدستورية، لأن التفسير والرقابة الدستوريين، هي من صميم الاختصاص الحصري لجهة الرقابة الدستورية المنعقد للمحكمة الدستورية بالمغرب، تونس والجزائر، وللمجلس الدستوري بفرنسا وفي الجزائر سابقا قبل التعديل الدستوري لسنة 2020. كرس المؤسس الدستوري التونسي في دستور 2014 ودستور 2022 الدور السلبي لقاضي الموضوع بما في ذلك قاضي الدرجة العليا بمحكمة التعقيب، الذي ينحصر دوره في إرسال الدفع إلى المحكمة الدستورية التونسية دون تفحصه، وتتولى هذه الأخيرة تصفيته من الناحية الشكلية عن طريق هيئة على مستواها قبل الفصل في مسألة الدستورية، وذلك على عكس المؤسس الدستوري الفرنسي، الجزائري والمغربي الذين كرسوا الدور الإيجابي لقاضي الموضوع بالجهات القضائية من خلال إقرار التصفية المزدوجة للدفع والإحالة، كما جعل اختصاص القاضي الدستوري متوقف على إحالة الجهة القضائية العليا كآلية للإخطار. يرتب قرار قاضي الموضوع بإرسال الدفع للجهة القضائية العليا أو أمر إحالة الدفع من قبل هذه الأخيرة على جهة الرقابة الدستورية وقف السير في دعوى الموضوع إلى غاية الفصل في الدفع من قبل الجهة المختصة، باستثناء حالة الاستعجال أو كان الشخص محروما من الحرية، وهو الأمر الذي كرسته القوانين الخاصة بالدول محل الدراسة كأصل واستثناء، كما أن قرار جهة القضاء الدستوري يحوز الحجية المطلقة، ويترتب عليه تحصن النص القانوني بقرينة الدستورية أو استبعاده من التطبيق على موضوع النزاع المعروض على القضاء بحسب قرارها، وبالتالي تنقيته من النظام القانوني اعتبارا من التاريخ الذي تحدده جهة القضاء الدستوري، وهو ما يؤسس لعلاقة تكاملية بين القضاء العادي والقضاء الدستوري، عن طريق التعاون المتبادل الذي توفره التصفية من تخفيف العبء على جهة الرقابة الدستورية بتفحص الدفع شكلا وموضوعا بنظر مسألة الدستورية ظاهريا بصفة عرضية، دون إغفال ما توفره الإحالة في تفعيل العدالة الدستورية من قبل الجهة القضائية العليا، وللطابع القضائي لقرارات جهة القضاء الدستوري لاسيما الحجية والقوة الإلزامية. بينت التجربة العملية والتطبيقية أن الجزائر سباقة في تفعيل الآلية مقارنة بالمغرب وتونس، وذلك لحالة الجمود التي تعاني منها آلية الدفع بعد التصريح بعدم دستورية القانون التنظيمي المغربي المنظم لآلية الدفع من قبل المحكمة الدستورية المغربية، ولعدم تنصيب المحكمة الدستورية التونسية ليومنا هذا، كما يتجلى من قرارات القضاء الدستوري الفرنسي والجزائري أن القاضي ليس لديه "الكلمة الأخيرة" لإسناد المعنى إلى القانون أو الدستور، حيث يتم تفسيرهما بشكل مشترك ومتزامن من قبل قضاة النظام العادي والقاضي الدستوري، هذا الأخير يملك سلطة حسم المسألة الدستورية باعتماد تفسيره لما تكتسيه قراراته من حجية وقوة ملزمة، وخلال عملية التفسير يبرز وجود عملية مستمرة وغير مكتملة على حد سواء أثناء التقاضي، يتجلى من خلالها مدى تأثير العمل التفسيري (التأويلي) الذي يقوم به القاضي العادي والإداري على قرار المحكمة الدستورية. Abstracts This study deals with the role of the judge in the mechanism for defending unconstitutionality in France and the Maghreb countries, specifically Algeria, Morocco and Tunisia, which brought about a radical change in the exercise of the constitutional oversight body’s jurisdiction, especially through referral to it as a notification mechanism by activating constitutional justice, Once it is raised by the litigant before the judiciary before which the dispute is presented to argue that the legislative or regulatory provision is unconstitutional with the aim of excluding it from application because it violates the rights and freedoms guaranteed by the Constitution, or that it constitutes a basis for criminal prosecution, during which the subject judge (ordinary and administrative) plays in both France and Algeria. Morocco plays a pivotal role in bringing it to the constitutional judiciary, Payement is considered a procedural mechanism supervised by the judge, through the system of double preliminary liquidation of payment at the level of the lower and higher judicial authorities. The trial judge has a set of powers to send the payment to the higher judicial authority or to refer it by the latter to the constitutional oversight body or not. His authority expands when monitoring the formal conditions, while it is restricted and narrowed when monitoring the substantive conditions, especially exercising his discretionary and interpretive authority while assessing the existence of a condition. The seriousness of the payment that is made under the supervision of the higher judicial authority as it is the body evaluating its rulings, Likewise, the body charged with constitutional oversight is the authority competent to decide on the issue of constitutionality, because its discretionary authority is restricted by the controls established in the text of the constitution and organic laws, while its interpretive authority by applying the methods and techniques of constitutional interpretation is limited to the superficial aspect without delving into it to the point of resolving the issue of constitutionality, because interpretation and oversight Constitutionalists, it is within the exclusive jurisdiction of the constitutional oversight body held by the Constitutional Court in Morocco, Tunisia and Algeria, and the Constitutional Council in France and in Algeria previously before the constitutional amendment of 2020. The Tunisian Constitutional Institution enshrined in the 2014 Constitution and the 2022 Constitution the negative role of the subject judge, including the high-level judge in the Court of Cassation, whose role is limited to sending the claim to the Tunisian Constitutional Court without examining it, and the latter is responsible for liquidating it formally through a body at its level before deciding on the case. The issue of constitutionality, in contrast to the French, Algerian and Moroccan constitutional founders, who established the positive role of the subject judge in the judicial authorities by approving the double liquidation of payment and referral, and also made the jurisdiction of the constitutional judge dependent on referral to the higher judicial authority as a notification mechanism. The decision of the trial judge to send the defense to the higher judicial authority or the order to refer the defense by the latter to the constitutional oversight body shall result in the suspension of the trial case until the defense is decided by the competent authority, except in the case of urgency or if the person is deprived of liberty, which is the matter that The laws of the countries under study have established it as an origin and an exception, and the decision of the constitutional judiciary has absolute authority, and it results in the legal text being protected by the presumption of constitutionality or being excluded from application to the subject of the dispute presented to the judiciary according to its decision. Thus, purifying it from the legal system as of the date determined by the constitutional judiciary, which establishes a complementary relationship between the ordinary judiciary and the constitutional judiciary, through mutual cooperation that the liquidation provides in order to reduce the burden on the constitutional oversight authority by examining the payment in form and substance by considering the issue of constitutionality on the surface in an incidental manner. Without neglecting, what referral provides in activating constitutional justice by the supreme judicial authority, and the judicial nature of the decisions of the constitutional judiciary, especially their authenticity and binding force. Practical and applied experience has shown that Algeria is the first to activate the mechanism compared to Morocco and Tunisia, due to the state of stagnation that the payment mechanism suffers from after the Moroccan regulatory law regulating the payment mechanism was declared unconstitutional by the Moroccan Constitutional Court, and because the Tunisian Constitutional Court has not been installed to this day, as is evident from the decisions The French and Algerian constitutional jurisprudence states that the judge does not have the “final word” to attribute meaning to the law or the constitution, They are interpreted jointly and simultaneously by the regular judges and the constitutional judge. The latter has the authority to resolve the constitutional issue by adopting his interpretation due to the authority and binding force of his decisions. During the interpretation process, the existence of a continuous and incomplete process both during litigation is evident, through which the extent of The impact of the interpretive work carried out by the ordinary and administrative judge on the decision of the Constitutional Court.
دراسة مقارنة بين الدول المغاربية وفرنسا
أطروحة
Keywords: دور القاضي; الدفع بعدم الدستورية; سلطات القاضي; النص التشريعي; The role of the judge; the defense of unconstitutionality; the powers of the judge; the legislative text